BINOPtimal: a web tool for optimal chiral phosphoric acid catalyst selection. Issue 12 (22nd January 2019) - Reid, Jolene P.; Ermanis, Kristaps; Goodman, Jonathan M.
Abstract : A catalyst selection program, BINOPtimal, has been developed. Abstract : A catalyst selection program, BINOPtimal, has been developed. This interactive web tool selects the best performing chiral phosphoric acid catalysts from analysis of the starting materials, imine and nucleophile, on the basis of rules derived from the transformations within its database. This procedure has been applied to an example transformation demonstrating the potential to assist reaction design. The tool is available atwww-mmm.ch.cam.ac.uk .